Detecting and measuring of GPCR signaling – comparison of human induced pluripotent stem cells and immortal cell lines - Chen, Gaoxian; Obal, Detlef (Frontiers in Endocrinology, 2023)
G-protein-coupled receptors (GPCRs) are a large family of transmembrane proteins that play a major role in many physiological processes, and thus GPCR-targeted drug development has been widely promoted. Although research findings generated in immortal cell lines have contributed to the advancement of the GPCR field, the homogenous genetic backgrounds, and the overexpression of GPCRs in these cell lines make it difficult to correlate the results with clinical patients. Human induced pluripotent stem cells (hiPSCs) have the potential to overcome these limitations, because they contain patient specific genetic information and can differentiate into numerous cell types. To detect GPCRs in hiPSCs, highly selective labeling and sensitive imaging techniques are required. This review summarizes existing resonance energy transfer and protein complementation assay technologies, as well as existing and new labeling methods. The difficulties of extending existing detection methods to hiPSCs are discussed, as well as the potential of hiPSCs to expand GPCR research towards personalized medicine.